Job Satisfaction and Organizational Commitment among Private School Teachers in Nasugbu, Batangas: Basis for Improving Teachers’ Retention - Tiangco, Allan Noel G. (11th International Scholars Conference, 2018)
In the face of uncertainties, organizational handlers have come to the realization that organization’s success can no longer be sustained through improved products and services alone but through dedicated, satisfied and committed employees. The study investigated job satisfaction and organizational commitment among private school teachers in Nasugbu, Batangas. The sample consisted of 57 teachers from the different private schools in town. Statistical tools such as frequency, percentage, Pearson r correlation and analysis of variance (ANOVA) are utilized to analyze the data gathered. Findings revealed that private school teachers in Nasugbu, Batangas are very satisfied with their jobs and that they are committed to the organization. Result of correlation analysis suggested that there exists a moderate positive and significant correlation between job satisfaction and organizational commitment. It was also revealed that there is no significant difference among each of the profile variables of the respondents and their job satisfaction and organizational commitment. Based on the findings, the researcher recommends that the management continue to offer a fair and flexible promotional policies and opportunities and effective job advancement schemes; build effective communication; and give frequent and clear feedback to improve the employees’ perception of security and further improve their job satisfaction.